2011
DOI: 10.2174/1874838401104010001
|View full text |Cite
|
Sign up to set email alerts
|

Urticaria as Symptom of Parasite Migration Through the Biological Barriers

Abstract: Abstract:The absence of a consistent link between parasitoses and urticarial symptoms in the clinical investigations contrasts to the fact that some parasites are the most potent inducers of immunoglobulin E that exist in nature. To shed some light into this question, this review is focused on the actual knowledge regarding parasites life cycle, interactions with host immunity, the influence on host behavior, and finally the role of all these factors on the urticaria development. The collected data demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
7
0
1
Order By: Relevance
“…His CSU resolved completely after specific and effective treatment of the infection. Since then, infections with endoparasites, such as helminths (worms, which consist of many cells and have internal organs) and protozoa (consist of only one cell), have been discussed to cause chronic urticaria, and several clinical studies and reviews on the prevalence and relevance of PI in patients with CSU were performed and published .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…His CSU resolved completely after specific and effective treatment of the infection. Since then, infections with endoparasites, such as helminths (worms, which consist of many cells and have internal organs) and protozoa (consist of only one cell), have been discussed to cause chronic urticaria, and several clinical studies and reviews on the prevalence and relevance of PI in patients with CSU were performed and published .…”
mentioning
confidence: 99%
“…Many studies have linked CSU with PI , but the true rate of comorbidity, the role of parasites in CSU etiology, and the pathomechanisms in CSU due to PI are still unclear. Here, we review and evaluate the prevalence of PI in CSU and vice versa, we assess the role of PI as a cause of CSU and the effect of antiparasitic treatment on CSU, and we discuss possible pathomechanisms in CSU due to PI.…”
mentioning
confidence: 99%
“…Clinical investigations of the link between parasitosis and skin allergic symptoms are very limited, despite the fact that some parasites are among the most potent inducers of IgE production . Recent reports suggest that interaction between parasites and host immunity is more complex than previously understood, especially with reference to Trichuris muris , Strongyloides spp., Echinococcus spp., and Anisakis simplex . Mouse studies on the immune response to G. lamblia and Giardia muris showed that Giardia spp.…”
Section: Urticaria As Symptom Of Parasite Infectionmentioning
confidence: 99%
“…29 Recent reports suggest that interaction between parasites and host immunity is more complex than previously understood, especially with reference to Trichuris muris, Strongyloides spp., Echinococcus spp., and Anisakis simplex. 30 Mouse studies on the immune response to G. lamblia and Giardia muris showed that Giardia spp. can express different types of variant surface protein.…”
Section: Urticaria As Symptom Of Parasite Infectionmentioning
confidence: 99%
“…Thus, development of hyperreactive respiratory symptoms during common bacterial and viral infections after a "silent" incubatory period suggests that microorganisms may manipulate host immunity, allowing themselves a "safe escape" for a few days to do that, before the production of eradicative IgA or IgG antibodies [22]. While common microorganisms induce hyperreactive/allergic respiratory symptoms after their reproduction, massive infestation with various geohelminths in equatorial regions is associated with suppression of respiratory symptoms and a lower prevalence of atopic pathologies despite the potent IgE induction [1,21,[23][24][25][26][27][28][29]. The negative correlation of infective agent survival to the concentration of specific IgG1 and IgA suggests that in vivo, Th2 profile may not simply be a host-chosen reaction only, but also the most efficient and beneficial humoral response during host-infection interaction [30][31][32][33].…”
Section: The Role Of Infections In the Respiratory Atopymentioning
confidence: 99%